2018
DOI: 10.4317/jced.54469
|View full text |Cite
|
Sign up to set email alerts
|

Caries and quality of life in portuguese adolescents: Impact of diet and behavioural risk factors

Abstract: BackgroundThe aim of this study was to assess the impact of diet and behavioural risk factors on caries appearance, and on oral health-related quality of life (OHRQoL) among Portuguese adolescents.Material and MethodsAn epidemiological study conducted on 782 adolescents between 11-17 years, from randomly selected public schools of the 3rd cycle of basic education. All participants were asked for self-perceived general status health, about tooth-brushing habits and about the using of toothpaste with fluoride an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
1
17
1
6
Order By: Relevance
“…According to the latest data, brushing teeth just as often as twice a day was declared by young people from Sweden (77–86% girls and 71% boys) and Scotland (83% girls and 65% boys) [ 54 , 55 ]. Definitely lower rates of youths who brushed their teeth twice or more times a day were recorded in the Czech Republic (79.5% girls and 61.9% boys), in France (70.9%), in Portugal (65.1%) and in Australia (57%) [ 56 , 57 , 58 , 59 ]. In accordance with the results of other authors, we observed a significant difference between the genders referring to the frequency of toothbrushing [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest data, brushing teeth just as often as twice a day was declared by young people from Sweden (77–86% girls and 71% boys) and Scotland (83% girls and 65% boys) [ 54 , 55 ]. Definitely lower rates of youths who brushed their teeth twice or more times a day were recorded in the Czech Republic (79.5% girls and 61.9% boys), in France (70.9%), in Portugal (65.1%) and in Australia (57%) [ 56 , 57 , 58 , 59 ]. In accordance with the results of other authors, we observed a significant difference between the genders referring to the frequency of toothbrushing [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…La incorporación de la medición de la CVRSO en la evaluación integral de la salud oral es de suma importancia porque proporciona información esencial, al considerar las necesidades de tratamiento de individuos y poblaciones desde su propia perspectiva. También es una importante herramienta para la evaluación de intervenciones, servicios y programas de salud pública (Jokovic et al, 2002;Palencia et al, 2014) en especial aquellos que incluyen niños y adolescentes, dado que constituyen uno de los principales grupos objetivo de los servicios dentales (Montero et al, 2018).…”
Section: Introductionunclassified
“…Sin embargo, se podría suponer que un nivel alto de caries y especialmente con lesiones no tratadas, podrían generar un mayor malestar a lo largo de la vida de una persona, pudiendo esta generar una percepción negativa dentro de la calidad de vida (33). Es importante también mencionar que existen estudios que relacionan otros factores clínicos como la situación de salud general, los conductuales, periodontales y estéticos como impactó en la CVRSO (34,35).…”
Section: Discussionunclassified